Safety Risk Analysis and Protective Control of Existing Pipelines Affected by Deep Pit Excavation in Metro Construction - Bin Hu; Xiaoqing Li; Dan Huang (Modelling and Simulation in Engineering)
Urban underground pipelines undertake many tasks closely related to people’s daily life and production, such as water supply, drainage, gas supply, and power supply. Metro projects are usually located in areas with dense underground pipelines; therefore, in the construction process of deep-foundation metro pit, some measures should be taken to protect the safety of underground pipelines. Under the engineering background of the Jiangbei foundation pit of the Wuhan Yangtze River Tunnel, the influence of soil disturbance caused by deep-foundation pit excavation is first simulated using the ABAQUS software on the displacement of underground pipelines and the dangerous area of underground pipelines is analyzed. Second, the most disadvantageous combination is analyzed for the risk factors of pipelines under the influences of multiple risk factors. Finally, a systematic additional partial reinforcement scheme (APRS) is proposed from the aspects of safety and economy to protect the safety of underground pipelines in the dangerous areas with greater risk. The results of measurement prove that the APRS is effective for pipeline protection and can provide reference for similar problems.